Information systems support appropriate research operations for decision making Sisaket Rajabhat University - Chakkabud, Arisaphat (Research and Development Journal Sisaket Rajabhat University, 2026)
The information system supporting appropriate research operations for decision making at Sisaket Rajabhat University was developed with the following objectives: (1) to study and develop an information system to support research operations for decision-making at Sisaket Rajabhat University, and (2) to evaluate the efficiency of the developed information system. The sample group used in the research was 30 experts, operational staff, lecturers, and researchers at Sisaket Rajabhat University. The selection was done by purposive sampling. The tool for evaluating the system efficiency used a five-point rating scale questionnaire completed by computer experts, operational staff, and committee members. The statistics used for data analysis were mean and standard deviation. The findings revealed that: 1. The developed information system should be structured into three user groups: 1) practitioners 2) lecturers/researchers 3) general public. Each user group is assigned different access privileges. The developed system can store, edit, delete, upload, search for up-to-date online data, and provide an online search function that allows users to retrieve both current and historical information at any time. The information system is updated to be current and the system administrator updates the data regularly. The information system can view the research project database, the publication of researchers, the publication of research results and publications, the publication of innovation and invention data, and the publication of research service area data. The system can be accessed at any time, and documents can be downloaded for immediate use. 2. The efficiency evaluation conducted by experts, operational staff, lecturers/researchers, and members of the general public indicated that the developed system achieved a high level of efficiency. The system was found to be appropriate, consistent with users’ needs, and suitable for practical implementation.